The role of innate immune system in respiratory viral infection related asthma - Wu, Xiao; Huang, Feifei; Yao, Wenbo; Xue, Zheng (Frontiers in Cellular and Infection Microbiology, 2025)
The association between viral infections and asthma has garnered significant attention in recent years. Accumulating evidence suggests that viral infections can trigger asthma exacerbations, while asthma may also influence the susceptibility to viral infections, thereby creating a cycle of worsening symptoms and recurrent asthma attacks. Given that asthma is predominantly driven by Type 2 immune responses and viral infections are typically associated with Type 1 immune responses, the innate immune cells and cytokines that participate in both conditions appear to be the critical bridge connecting these two processes. In particular, innate immune cells play a pivotal role in modulating the immune response at the interface of viral infections and asthma. In this review, we summarize the key innate immune cells and cytokines involved in viral infections and asthma, highlighting their immunoregulatory mechanisms. We aim to provide novel perspectives and potential therapeutic directions for the clinical management of recurrent asthma attacks induced by viral infections.